PERAN PENDIDIKAN ISLAM DALAM MEMELIHARA KEBERAGAMAN BUDAYA DAN IDENTITAS KOLEKTIF - Ahmad Jamal; Acep Rahmat Acep Rahmat; Muhammad Ihda Hidayatur Ramadan; Muhammad Sulaiman Al-Muzzamil (Advances In Education Journal, 2024)
This study aims to understand the role of education in preserving cultural diversity and group identity. The research employs a literature review method, gathering research sources from articles, journals, and books relevant to the topic of discussion. The findings reveal that Islamic education plays a crucial role in addressing several issues, such as juvenile delinquency and crimes committed by minors, as these problems significantly impact social life. Therefore, one solution to these challenges is through multicultural education, specifically the "Merdeka Belajar" (Freedom to Learn) program, which includes P5P2RA, emphasizing global diversity character education. Additionally, the study highlights two key aspects: first, the role of school principals, who must support all aspects of the school to achieve quality education; and second, the role of teachers, who play a vital role in multicultural education by implementing effective strategies to understand multicultural education concepts.  The impact of these efforts, through the principal's role in implementing the "Merdeka" curriculum via P5P2RA, is positive, as students gain extensive knowledge about cultural diversity.